Emotional Design: Direction for Application of Idea to Design of Equipment for Keeping Dining Utensils - Sompoangeon, Saneh; Busamsai, Vorachat; Siriwangkaung, Surachet (Journal of Fine and Applied Arts Khon Kaen University, 2024)
The objectives of this research work are 1) to design the equipment for keeping dining utensils with the application of the idea of emotional design; and 2) to evaluate the satisfaction toward the prototype of the equipment for keeping dining utensils. The tools used are 2 sets of questionnaires. The samples are 100 consumers, selected with purposive sampling technique through online system. The statistic values used for analysis are percentages, means and standard deviations, the findings from the research show the following facts. 1) The application of emotional design approach (in visceral, behavioral and reflective levels) affects the directions for designing the product (external appearance, utility, story or meanings) for the anticipation of consumers’ responses (attractiveness, convenience and image reflection or self-communication) and the implementation of mind map to develop shape and form of the equipment to form up the “Love and Care” concept, through human gestures and behaviors that show love and affection though hand holding and hugging. Afterwards, 3 styles of prototype equipment are designed. The prototypes with the highest total scores are style 2, which are appropriate in the high level (𝑥̅ = 4.24, S.D. = 0.55). 2) The outcomes from the evaluation of the samples’ satisfaction toward the designed equipment show that the overall satisfaction is in high level (𝑥̅ = 4.15, S.D. = 0.67). The satisfaction toward the category of emotion is in high level (𝑥̅ = 4.10, S.D. = 0.68). The following category is the design, with has the satisfaction in high level as well (𝑥̅ = 4.20, S.D. = 0.66). As for the category of emotion and feeling that the consumers are most satisfied with is the feeling of attractiveness since the first time the consumers see the product, with satisfaction level in high level (𝑥̅ = 4.40, S.D. = 0.60). As for the category of design, the consumers are most satisfied with uniqueness and identities that are different, with satisfaction level in high level (𝑥̅ = 4.37, S.D. = 0.63). From the results from the evaluation, the prototypes of the equipment can trigger the consumers’ feelings though seeing external shapes, which has reflected the perception in the visceral level in the efficient manner, which will further create the perception in behavioral and reflective levels in the future.